(untitled) (Environment & Health, 2021)
Objective: We performed sanitary-and-epidemiological and ecological-and- hygienic substantiation of the conditions for the location of low-capacity enterprises for the manufacture of asphalt concrete, developed the hygienic criteria for their location taking into account the newest home sanitary, ecological and town-planning legislations and requirements of the European Union directives. Materials and methods: In the article we used results of sanitary-and-epidemiological examination of the project materials and applied bibliosemantic, analytical methods. Results: Тhe sanitary legislation of Ukraine of 1971 and 1996 in the normalization of sanitary-and-protection zone for the above mentioned enterprises was analyzed and compared with the analogous standards in the European countries. According to the results of the scientific sanitary-and-epidemiological examination of the project materials on the substantiation of the sanitary-and-protection zone for home low-capacity enterprises for the manufacture of asphalt concrete (80% of them were put into operation before 1996), the following was established. All investigated enterprises work with the prepared bitumen with the implementation of nature protection measures by means of the use of high-efficiency dust and gas cleaning systems, that shortened the gross emissions of the pollutants in ambient air to a large extent and decreased influence on the environment and adjoining settlement territory, that complies with the requirements of the Directive of 2010/75/EС of European Parliament and Council on the industrial emissions (integrated prevention and control of contamination), November 24, 2010. Implementation of nature protection measures with the use of the high-efficiency dust and gas cleaning systems at the existent low-capacity enterprises for the manufacture of asphalt concrete provided the absence of the exceed of MPC of the specific pollutants at the distances that were 1.5-3.0 times less than standard sanitary-protective zone that was a cause for the substantiation of the use of new approach at the establishment of sanitary-and-protection zone by the calculation method at building of the new or reconstruction of the existent low-capacity enterprises for the manufacture of asphalt concrete.